Experimental and Theoretical Study of the 5s\(^2\)5p\(^3\) and 5s\(^5\)p\(^4\) Configurations in Sb-like Cerium - Wajid, Abdul; Jabeen, S. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
In this paper the ground and first excited configurations of Ce VIII have been studied, both experimentally and theoretically. The spectra of cerium have been photographed using a spark source on a normal incident spectrograph, equipped with a grating having the reciprocal dispersion of 1.38 í…/mm in the first order. The ground configuration has been established experimentally for the first time. The GRASP2018 package has been used to calculate energy levels, wavelengths and transition rates for the 5s\(^2\)5p\(^3\) and 5s\(^5\)p\(^4\) configurations. The electron correlation effects, Breit interaction and quantum electrodynamics effects have been considered in the calculation. The experimentally established energy levels have been compared with their theoretical values.